A New Mathematical Model for Assembly Line Worker Assignment and Balancing - Yılmaz, Hamid; Demir, Yunus (Igdir University, 2019)
Aim of assembly line balancing is to assign the product parts to the workstations that constitute the assembly line. Worker assignment problem is a new problem variety in assembly lines that typically is met in different situations in which the workforce is not homogeneous. This problem is different from the well-known simple assembly line balancing problem from the view point of task execution times of nonhomogeneous workers. In this paper, we introduce a new mathematical formulation with objective function to minimize the cycle time for the assembly line worker assignment and balancing problem (ALWABP). GUROBI solver is used for the problem solution. The mathematical model is examined by using a standard test problem set. As a result of the experiments, it is observed that the proposed mathematical model is more effective in terms of solution quality and CPU time than the current mathematical method.

Aim of assembly line balancing is to assign the product parts to the workstations that constitute the assembly line. Worker assignment problem is a new problem variety in assembly lines that typically is met in different situations in which the workforce is not homogeneous. This problem is different from the well-known simple assembly line balancing problem from the view point of task execution times of nonhomogeneous workers. In this paper, we introduce a new mathematical formulation with objective function to minimize the cycle time for the assembly line worker assignment and balancing problem (ALWABP). GUROBI solver is used for the problem solution. The mathematical model is examined by using a standard test problem set. As a result of the experiments, it is observed that the proposed mathematical model is more effective in terms of solution quality and CPU time than the current mathematical method.
A New Mathematical Model for Assembly Line Worker Assignment and Balancing
Keywords: Electrical Engineering; Elektrik Mühendisliği